2009
DOI: 10.2466/pr0.104.3.796-806
|View full text |Cite
|
Sign up to set email alerts
|

Association of Depression and Anxiety with Oocyte and Sperm Numbers and Pregnancy Outcomes during in vitro Fertilization Treatment

Abstract: To estimate association of depression and anxiety scores with oocyte and sperm numbers and pregnancy rates during in vitro fertilization (IVF) treatment, 80 Turkish couples were administered the Spielberger State and Trait Anxiety and Beck Depression Inventories. A significant correlation (r = -.25) obtained between Depression and women's oocyte pickup data and number of oocytes, showed that low oocyte numbers w ere associated with higher Depression. No significant relation was found for sperm counts with Anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…However, it also has been confirmed that IVF is a highly stressful experience (5). Stress and distress have been found to be associated with a poorer ovarian functional response to IVF-treatment and with reduced fertilization, implantation, and live-birth rates (8,21). Differences in population and choice of questionnaires may explain the conflicting results.…”
Section: Discussionmentioning
confidence: 91%
“…However, it also has been confirmed that IVF is a highly stressful experience (5). Stress and distress have been found to be associated with a poorer ovarian functional response to IVF-treatment and with reduced fertilization, implantation, and live-birth rates (8,21). Differences in population and choice of questionnaires may explain the conflicting results.…”
Section: Discussionmentioning
confidence: 91%
“…The screening process is summarized in the study PRISMA flow chart (Figure 1). A total of 11 studies Gourounti et al, 2011;Gürhan et al, 2009;Hashemi et al, 2012;Karlidere et al, 2008;Li et al, 2011;Lintsen et al, 2009;Saravelos et al, 2016;Taguchi et al, 2015;Turner et al, 2013;Zaig et al, 2012) were included in the meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%
“…Women undergoing infertility treatments exhibit high anxiety and/or high depressive scores at the start of treatment as well as over the course of treatment (1)(2)(3)(4). Stress may also have a negative impact on pregnancy rates in women undergoing in vitro fertilization (IVF) (5)(6)(7)(8). A recent large study (9) did not reveal a relationship between distress and IVF outcome, so it is possible that there might be differences among patient populations or cultural influences on emotional expression.…”
mentioning
confidence: 96%